Communication and information needs about complementary and alternative medicine: a qualitative study of parents of children with cancer - Stub, Trine (BMC Complement Med Ther, 2021)
BACKGROUND: Many parents choose support such as Complementary and Alternative Medicine (CAM) for themselves and their children who have cancer. The aim of this paper is to describe, how parents who have children with cancer communicated with conventional health care providers about CAM, and what types and sources of information they would like to receive about CAM when the child was ill. METHOD: This focused ethnography draws from in-depth, semi-structured interviews conducted with 22 families in Norway with 24 adult participants (two couples), including two individuals who had had cancer themselves. Four domains were explored in the data analysis: the use of CAM, advice from laypeople about CAM, communication with conventional health care providers about CAM, and parents’ information needs about CAM. RESULTS: Many of the participants had personal experiences with CAM before the child received the cancer diagnosis. The health care providers did not raise the question about CAM in the consultations. However, when the parents raised the question, they were mostly met in a positive way. The participants did not receive any information about CAM at the hospital, which they would have appreciated. Instead, they received recommendations about CAM from laypersons, which were mostly rejected, as the advice was not in line with their health values/philosophy. CONCLUSION: The reason participants did not disclose CAM use is that physicians did not ask them about it. However, positive communication about conventional treatment facilitated fruitful conversations about CAM. The participants wanted information about CAM from authoritative sources, primary from health care providers at the hospital and the Children’s Cancer Society. They demand information about risks and benefits when using CAM as well as whether CAM can improve the immune system, fight the cancer, and improve the quality of life of the family. An evidence-based decision aid is warranted to enable health care providers and parents of children with cancer to make well-informed decisions about CAM. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12906-021-03253-x.